Advanced Ann Arbor stage and age over 60 years as prognostic predictors in patients with primary cervical lymphoma: a retrospective cohort study and systematic review - Lingyun Gao; Xiaoran Chen; Jing Zhao; Anli Xu; Meijuan Liu; Hongna Yu; Shujun Kong; Sijian Li (BMC Cancer, 2023)
Abstract Objective To evaluate the overall survival (OS), disease-specific survival (DSS), and recurrence-free survival (RFS) for primary cervical lymphoma (PCL), an extremely rare disease without treatment consensus. Methods We conducted a retrospective study included 177 patients, including 169 cases identified from literature review. The Kaplan-Meier methods and Cox regression were used to determine the OS, DSS, RFS, and relevant risk factors. Results The 5-year OS and 5-year DSS rates were 85.8 and 87.2%, respectively, while the 5-year RFS rate was 85.5%. Diffuse large B-cell lymphoma (DLBCL) was the predominant subtype that comprised 63.8% (113 cases) in this cohort. Multivariate analysis in the DLBCL subgroup revealed that age ≥ 60 years (Odds ratio [OR]: 26.324, 95% Confidence Interval [CI]: 5.090–136.144, P < 0.001) or stage IIIE-IVE (advanced stage) (OR: 4.219, 95%CI: 1.314–13.551, P = 0.016) were the risk factors for OS, while patients with age ≥ 60 years (OR:23.015, 95%CI: 3.857–137.324, P = 0.001), and stage IIIE-IVE (OR: 4.056, 95% CI: 1.137–14.469, P = 0.031) suffered a poor DSS. Chemotherapy and/or radiotherapy improved the OS (P = 0.008), DSS (P = 0.049), and RFS (P = 0.003). However, cancer-directed surgery did not improve the OS, DSS, and RFS. The risk factor was unavailable in other subtypes of PCL due to limited cases. Conclusion The survival outcomes in patients with PCL at early stage were satisfactory, while the advanced disease stage and age ≥ 60 years were the two major factors predicting poor prognosis in DLBCL subtype.